Transforming growth factor beta1 and additional renoprotective effect of combination ACE inhibitor and angiotensin II receptor blocker in hypertensive subjects with minor renal abnormalities: a 24-week randomized controlled trial - Scaglione, Rosario; Argano, Christiano; Corrao, Salvatore; Di Chiara, Tiziana; Licata, Anna; Licata, Giuseppe (Journal of hypertension, 2005)
To verify the benefit of renin-angiotensin system blockade in hypertension, the effects of 24 weeks' losartan and ramipril treatment, both alone and in combination, on urinary albumin excretion (UAE) and circulating transforming growth factor beta1 (TGF beta1) have been evaluated in hypertensive subjects with minor renal abnormalities. Fifty-one patients with stage 1 and 2 essential hypertension and with UAE > or = 20 mg/24 h but with maintained renal function have been included. After a 4-week run-in with placebo administration, a randomized double-blind, three-arm double-dummy trial was used. All the hypertensives (HT) were allocated randomly to three treatment arms (17 patients for each group) and they were single-matched for age, gender, body mass index (BMI), systolic and diastolic blood pressure. Active treatment consisted of losartan (50 mg/day), ramipril (5 mg/day) and combined (losartan 50 mg/day plus ramipril 5 mg/day) for 24 weeks. Hydrochlorothiazide 12.5 mg/day was added in HT patients with uncontrolled blood pressure (> or = 140/90 mmHg) during the active treatment period. In all patients UAE, by immunonephelometric assay; circulating TGF beta1 by a solid-phase specific sandwich enzyme-linked immunosorbent assay (ELISA); and blood urea nitrogen (BUN), creatinine and creatinine clearance and potassium, by routine laboratory methods, were determined after placebo treatment and 24 weeks follow-up. The three treatment groups were comparable for gender, age, BMI, blood pressure, UAE and renal function measurements. During the active treatment period it was necessary to add hydrochlorothiazide in five patients--two each of the losartan and ramipril groups and one of the combined group. At the end of treatment, significant (P < 0.05) reductions in systolic, diastolic and mean blood pressure, UAE and TGF beta1 levels were observed in all the groups. No change in renal function measurements were observed. The absolute and percentage reduction in UAE and TGF beta1 were significantly higher in the combined group than in the losartan or ramipril groups. No significant changes in absolute and percentage reduction of systolic, diastolic and mean blood pressure were found. All treatment regimens were well tolerated with few and transient side-effects. These data indicate an additional renoprotective effect of dual blockade of the renin-angiotensin system (RAS) in hypertensive patients with minor renal abnormalities. In addition, the contemporaneus and marked decrease in TGF beta1 and UAE levels in hypertensives treated with combined therapy might indicate the presence of a subset of subjects who may benefit from complete RAS blockade.